2006
DOI: 10.7150/ijbs.2.10
|View full text |Cite
|
Sign up to set email alerts
|

NAD(H) recycling activity of an engineered bifunctional enzyme galactose dehydrogenase/lactate dehydrogenase

Abstract: A chimeric bifunctional enzyme composing of galactose dehydrogenase (galDH; from Pseudomonas fluorescens) and lactate dehydrogenase (LDH; from Bacillus stearothermophilus) was successfully constructed. The chimeric galDH/LDH possessed dual characteristics of both galactose dehydrogenase and lactate dehydrogenase activities while exhibiting hexameric rearrangement with a molecular weight of approximately 400 kDa. In vitro observations showed that the chimeric enzyme was able to recycle NAD with a continuous pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
(36 reference statements)
1
16
1
Order By: Relevance
“…It had been reported that the fusion of two multimeric enzyme could lead to the formation of multimeric protein network which may cause steric hindrance of active domain. Soluble bi‐functional enzyme compose of two multimeric enzyme have reported to form oligomers . LeuDH and FDH in our study usually formed octamer and dimer, respectively.…”
Section: Resultssupporting
confidence: 46%
“…It had been reported that the fusion of two multimeric enzyme could lead to the formation of multimeric protein network which may cause steric hindrance of active domain. Soluble bi‐functional enzyme compose of two multimeric enzyme have reported to form oligomers . LeuDH and FDH in our study usually formed octamer and dimer, respectively.…”
Section: Resultssupporting
confidence: 46%
“…As an alternative to using two separate enzymes, bifunctional fusion proteins can be constructed in which the production enzyme and the cofactor‐regenerating enzyme are connected through a linker sequence to yield a single polypeptide exhibiting both catalytic activities (). Although the advantages of fusion proteins composed of enzymes that catalyse sequential reactions have been studied since the late 1980s [8,9], this technique has recently been ‘rediscovered’ as a beneficial tool for cofactor recycling [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…First, several protein fusions consisting of sequential enzymes have been characterized in vitro and shown to possess kinetic properties superior to those of the individual enzymes (6,7,22,29). Second, experiments carried out with purified fusion proteins in polyethylene glycol solutions to mimic the crowded environment inside the cell indicate that the positive effects of enzyme fusion may be even greater in vivo (38,25,5). Last, the production of geranylgeraniol in S. cerevisiae was significantly increased by overexpressing a fusion of the yeast proteins Bts1 and Dpp1 (33).…”
mentioning
confidence: 99%